2012
DOI: 10.1007/bf03261884
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid in the Treatment of Knee Osteoarthritis

Abstract: In the future it will be important to determine the exact mechanism of action of placebo as this may give us an idea of how to treat osteoarthritis more efficiently. Due to the limitations of this review (follow-up of just 3 months and large heterogeneity of the included studies), it is also important to compare the different HA products to determine which product(s), or which molecular weight range, concentration, or volume of HA is the best option to treat osteoarthritis. Our recommendation is to start large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 76 publications
1
42
0
6
Order By: Relevance
“…Three RCTs [22, 29, 34] and 13 observational studies (reported in 16 articles [3550]) reported on TKR, but evidence on delay or avoidance of TKR was insufficient to draw conclusions. Two large, good quality systematic reviews with meta-analyses for pain outcomes showed a significant and clinically important effect among adults of all ages [8, 51]. …”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs [22, 29, 34] and 13 observational studies (reported in 16 articles [3550]) reported on TKR, but evidence on delay or avoidance of TKR was insufficient to draw conclusions. Two large, good quality systematic reviews with meta-analyses for pain outcomes showed a significant and clinically important effect among adults of all ages [8, 51]. …”
Section: Resultsmentioning
confidence: 99%
“…In a previous study involving 57 patients following knee arthroscopy, the same group demonstrated equal efficacy in pain relief whether saline alone or saline with 2mg morphine were IA injected into the knee [7]. In a systematic review and meta-analysis of 74 randomized clinical trials for the treatment of OAK with hyaluronic acid, it was concluded that saline has a “large placebo effect” of approximately 30% pain reduction [8]. Other meta-analyses of randomized controlled trials have demonstrated that the administration of IA saline significantly improves short-term (≤ 3 months) and long-term (6-12 months) knee pain, improves function, and decreases stiffness [9, 10].…”
Section: Analgesic Effects Of Salinementioning
confidence: 99%
“…HA is a hydrophilic dipolysaccharide with a very high molecular weight (200kDa~325kDa in this study). HA has been used for a wide variety of medical applications including osteoarthritis [15], embryo implantation [16], and cutaneous wound healing [17, 18]. In dermatology and cosmetic practice, HA has been employed to help the skin to regain elasticity, turgor and moisture [19].…”
Section: Introductionmentioning
confidence: 99%